TINJAUAN YURIDIS PUTUSAN MAHKAMAH AGUNG NOMOR 23P/HUM/2024 TERKAIT UJI MATERIIL TERHADAP PERATURAN KOMISI PEMILIHAN UMUM NOMOR 9 TAHUN 2020 - NIM. A1011211258, ISKANDAR (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract The Supreme Court has issued Decision Number 23P/HUM/2024 concerning the judicial review of the General Election Commission Regulation Number 9 of 2020, specifically Article 4 Paragraph (1) letter d, which relates to the age requirement for regional heads. This decision has sparked controversy, as the Supreme Court is not authorized to interpret the substance of legal norms. Moreover, the rationale and considerations used by the justices in delivering the verdict are viewed by many as inappropriate and insufficiently grounded. Based on this, the research problem formulated in this study is: